Uvajanje avtomatizacije v NUK in v slovenske javne knjižnice - Bahor, Stanislav (Knjižnica, 2006)
The article describes further efforts to implement library automation in the Slovene National and University Library and other libraries in the period from 1977 to 1979. The attempts to transfer the theoretical knowledge into the practice were characterized by difficult economic situation, chronic lack of funds for carrying out library activities, lack of library staff, a complicated system of reaching the agreement on the measures to be taken and a set of administrative restrictions. In spite of these barriers, some pilot projects for the implementation of computers in libraries have been carried out, related with a great deal of improvisation and optimal exploitation of the available technology. In accordance with the medium-term plan og library automation, the National and University Library performed a practical test of the input of monographs'records based on the specially designed system format (SAIDC) for data record in order to build the automated central catalogue. The procedures for the preparation of research projects' data entry were designed and the entry of about 1.300 research projects into the database were carried out. Search and retrieval of information, and the printing of the bulletins with appropriate indexes were enabled. The practical results were presented to the professional public.
Keywords: javne knjižnice; Narodna in univerzitetna knjižnica; National and University Library of Slovenia; Ljubljana; avtomatizacija; 1977/1979